HUBUNGAN ANTARA AKTIVITAS BERKENDARA SEPEDA MOTOR DAN KELUHAN PERNAPASAN PADA MAHASISWA UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Muhamad Zainaldi (2020)
Based on the results of air pollutant index measurements, the city of Jakarta is currently categorized as unhealthy, so that all activities outside the home such as driving a motorcycle can be at risk of causing respiratory complaints. Some students of the University Pembangunan Nasional Veteran Jakarta before the pandemic, did their college activities by riding a motorcycle to campus, this could be at risk of experiencing respiratory complaints due to sucking air containing pollutants. The purpose of this research find out the correlation between driving motorcyle activity and respiratory disease complaints. Type of quantitative research with cross sectional research design with incidental sampling technique. Variables of research: respiratory complaints, sex, history of respiratory disease, duration of driving, smoking behavior, and mask use. Data collection using a questionnaire tool with google form results will be analyzed univariate and bivariate. The results of the chi square test in this research stated that there is a correlation between the history of respiratory disease and respiratory complaints in students who ride motorcycles. Conclusions related variables are history of respiratory disease P value = 0,0001 ( OR = 6,533 ; 90% CI 2,704 - 16,147 ) and are not related variables are gender, driving duration, smoking behavior and mask use.